PENERAPAN STANDAR OPERASIONAL PROSEDUR CHECK IN TAMU INDIVIDUAL OLEH GUEST EXPERIENCE ASSISTANT PADA MASA PANDEMI COVID 19 DI THE SEMINYAK BEACH RESORT & SPA BALI - Polikarpus.N, Pondang; Utami, Ni Ketut Chanra Yogi; Widhiastuty, Ni Luh Putu Sri; Prayogi, Putu Agus (HARMONY HOSPITALITY, 2022)
The purposes of this study are as follows: 1. to find out the standard operating procedures for individual guest check-in during the Covid-19 pandemic, 2. to find out the application of standard operating procedures for individual guest check-in by guest experience assistants during the Covid-19 pandemic , 3. to find out the obstacles experienced by guest experience assistants in implementing standard operating procedures for individual guest check-in during the Covid-19 pandemic, 4. to find out the efforts made to overcome obstacles in implementing standard operating procedures for individual guest check-in during the Covid-19 pandemic at The Seminyak Beach Resort & Spa. The analysis technique used in this study is a qualitative descriptive analysis technique. The research instruments are: observation check-list, documentation study, and interview list. From the results of the research that has been done, several conclusions can be drawn as follows: 1. 1. The standard operating procedures for individual guest check-in during the Covid-19 pandemic at The Seminyak Beach Resort & Spa underwent several additions and new arrangements referring to CHSE, 2. the application of health protocols to standard operating procedures for individual guest check-in has not been carried out optimally and consistently because some of the standard operating procedures are not carried out by guest experience assistants, 3. Constraints experienced include: lack of employees, some guests are still difficult to maintain distance, 4. efforts made in dealing with obstacles include: dividing tasks with trainees, putting up signs keeping distance